Spatial variability of the Rotterdam urban heat island as influenced by urban land use. Issue 2 (31st January 2014) - Heusinkveld, Bert G.; Steeneveld, G. J.; van, L. W. A.; Jacobs, C. M. J.; Holtslag, A. A. M.
Abstract Novel bicycle traverse meteorological measurements were made in Rotterdam to assess the spatial variation of temperature during a tropical day. Nocturnal spatial urban temperature differences of 7 K were found to be related to city morphology. During midday measurements, the downtown was up to 1.2 K warmer than the surrounding rural area while a city park was 4.0 K cooler than downtown. A regression analysis showed that the nocturnal measured urban heat island (UHI) can be linked to land use, namely vegetation, built‐up area, and water and is most significant for vegetation. From the traverse observation data, a multiple linear regression model was constructed and independently validated with 3 year summertime UHI statistics derived from four urban fixed meteorological stations and two fixed rural stations. Wind rose analysis shows that UHI is strongest from easterly directions and that the temperature signal of the WMO station is influenced from urban directions. A regression model reproduced the nighttime spatial variability of the UHI within a fractional bias of 4.3% and was used to derive an UHI map of Rotterdam and surroundings. This map shows that high‐density urban configurations lacking greenery or close to large water bodies are vulnerable to high nocturnal temperatures during heat waves. The UHI map can be used as a valuable planning tool for mitigating nocturnal urban heat stress or identifying neighborhoods at risk during heat waves.